Water Absorption And Tensile Properties Of Kenaf Bast Fiber- Plasticized Poly(Lactic Acid) Biocomposites. - Mat Taib, R; Ramarad, Suganti; Mohd Ishak, Z A; Todo, M (2008)

(untitled)
Abstract - Increasing awareness on the environmental safety coupled with new rules and regulations has forced manufacturers to consider biodegradable materials for their products.The aim of this work was to investigate tensile properties and water absorption behavior of biocomposites from kenaf bast fiber and poly(lactic acid).The composites were prepared by Haake internal mixer and compression molding.